2001
DOI: 10.1046/j.1460-9592.2001.00194.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Aging on AV Nodal Recovery Properties

Abstract: The purpose of this study was to assess the changes of AV nodal recovery properties with aging. Although in children and young adults it was found that there were age dependent changes in their AV nodal recovery properties, in the older population this information was not available. In 92 subjects (aged 16-92 years) without AV nodal disease or dual AV nodal pathway physiology, their AV nodal recovery curves were studied by delivering premature atrial extrastimuli coupled to basic atrial beats during cardiac el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…It is well known that AV node conduction changes progressively with aging 20 . A slowing of AVNRT cycle length and an increase of AVN antegrade refractory period, of Wenchebach cycle length, and of P–R interval have been described, together with a decrease in overt dual AVN physiology pattern at EP study 20–22 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is well known that AV node conduction changes progressively with aging 20 . A slowing of AVNRT cycle length and an increase of AVN antegrade refractory period, of Wenchebach cycle length, and of P–R interval have been described, together with a decrease in overt dual AVN physiology pattern at EP study 20–22 .…”
Section: Discussionmentioning
confidence: 98%
“…On the basis of AVNRT induction modalities at EP study, two study groups were extrapolated: seven patients (group I: 6 females, 1 male; mean age 65.2 ± 3.8 years, range 60–72 years) who showed AVNRT induced through SDNC, and 118 controls aged 60 years or over (group II: 60 females, 58 males; mean age 68.4 ± 6.8 years, range 60–88 years) with AVNRT induced without SDNC. Such an age limit for recruiting controls was decided in order to have an overall matching by age with SDNC patients, since aging process consistently modifies AV node conduction properties 20–22 . Because of the presence of some very old control patients, group II controls were further subdivided into two subgroups: subgroup A, which consisted of 94 patients, aged 60–75 years (mean 65.8 ± 3.9 years; 53 females, 41 males); subgroup B, which consisted of 24 patients, aged more than 75 years (mean 80.3 ± 3.3 years; 8 females, 16 males).…”
Section: Methodsmentioning
confidence: 99%
“…7 The impact of these pathoanatomic changes on AV node function is uncertain; in fact, one small clinical study found that refractory periods of the AV node prolonged only slightly once adulthood was reached. 8 However, as discussed later, large population studies have consistently demonstrated progressive delay in AV conduction with age. It may be that aging has different effects on refractoriness and conduction velocity properties of the AV conduction system.…”
Section: Prevalence and Pathophysiology Of Bradyarrhythmias In The Elmentioning
confidence: 91%
“…In addition, pre-clinical studies in rabbits have shown an aging-related slowdown of electrical conduction velocity throughout the His-Purkinje network (8), which is manifested in humans by prolongation of the HV interval. Kuo et al (9) showed that the atrioventricular (AV) nodal recovery curve remains unchanged once one reaches adulthood, whereas the AV nodal effective refractory period becomes slightly longer after age 60 years (9). …”
Section: Pathophysiology Of Arrhythmias In the Elderlymentioning
confidence: 99%